0339 Effectiveness of Recruiting Type 1 Narcolepsy Patients via Internet Based Pre-selection System. (27th April 2018) - Roth, T; O'Daly, S; Fenton, M; Dowd, S; Cassidy, N; Allen, J; Monteith, D; Klassen, S
Abstract: Introduction: Rare disorders such as narcolepsy require casting a broad net to identify potential patients for clinical trials. The present report presents the results of an internet based pre-selection recruitment methodology to accomplish this. A collaboration between Flamel Ireland/Avadel Ireland and Link2Trials used this approach to identify type 1 narcolepsy patients for potential eligibility for a clinical trial. Methods: The link to the pre-selection website was available via internet search engines as well as social media websites. The link had potential participants respond to 11 questions regarding their eligibility for the trial. A unique aspect of this study is that the previous use of sodium oxybate was an exclusion criteria. Thus the link did not merely identify narcolepsy subjects, but rather narcolepsy patients with cataplexy without a negative history of sodium oxybate use. Results: 836 people successfully completed the 11 questions online. Of those, 205 (24.5%) were eligible and were referred on to the nearest investigative site. The main reasons for exclusion were past sodium oxybate use (n=268), comorbid medical/sleep disorder (n=252) and narcolepsy without cataplexy (n=250). Other exclusion reasons included no narcolepsy diagnosis (n=156), working nights or shift work (n=76), driving for a living (n=60), not willing to discontinue contraindicated medication (eg. anti-cataplexy medication) (n=28), not willing to discontinue alcohol (n=19), not meeting excessive daytime sleepiness requirements (n=11), pregnancy/breastfeeding (n=7) and not willing to use electronic diary (n=3). Conclusion: The use of an internet based pre-selection system, even for rare conditions such as type 1 narcolepsy was shown to be an effective screening method to identify potential subjects meeting specific entry criteria. For this study, 205 (24.5%) individuals who completed the survey were eligible for clinical trial participation. Support (If Any):